The Study of the Potential of Thai Food Recipes to be Developed as Food Menus to Teach Tourists - วิสุทธิแพทย์ โสรัจจ์; ฉายศิริโชติ ธีรนุช; ทองมี อรอนงค์ (Journal of Thai Food Culture, 2021)
The objectives of this research are 1) to study the favorite Thai food recipes for tourists and 2) to study the potential of Thai food recipes to be developed as food menus to teach tourists. The reseacher collected of information from textbook, articles and tourist questionnaires, interviews with Thai food experts, involved person from public and private sectors, studied of tourists needed, focus group and workshop. After that, using descriptive analysis for answering the objectives. Tools of this research were survey guide and interview with 6 experts, practitioner group and general (people and tourists) by using participant observation, non-participant observation, focus group discussion 6 people and workshop 6 people. The research result found that most foreign tourists are male between 35 - 44 years old. The highest number of tourists is from China. Tourists came to Thailand and stayed for 1 – 7 days. The perception of information about Thai food, Thai desserts and beverages found that respondents were knowledgeable about Thai food, Thai desserts and beverages in overall with high level and the respondents were aware that the identity of Thai food was mellow taste. The favorite beverage was coconut water, favorite curry was Green Curry, favorite soup was Tom Yum Goong, favorite stir fired chicken with Cashew Nut, favorite fried Spring Roll. Favorite salad was Papaya Salad, favorite a la carte was Pad Thai, favorite appetizer/dessert was Mango and Sweet Sticky Rice.